Combined and staged treatment of mesh erosion after hiatal hernia repair - Liangqi Lu; Xiangyu Shao; Junsheng Li (International Journal of Abdominal Wall and Hernia Surgery)
Mesh erosion following hiatal hernia repair is a rare but serious postoperative issue. It can lead to esophageal stenosis, gastric and esophageal fistulae, and may necessitate extensive surgical tissue removal and reconstruction. Therefore, employing minimally invasive and appropriate treatment strategies is crucial for patient management. We present the case of a 65-year-old woman who experienced mesh erosion after hiatal hernia repair. She underwent laparoscopic surgery followed by staged endoscopic treatment, resulting in complete removal of the mesh with preservation of organs and avoidance of major surgery. This combined laparoscopic–endoscopic approach represents an optimal method for managing such complications.